Synthetic bacterial vesicles combined with tumour extracellular vesicles as cancer immunotherapy - Park, Kyong-Su; Svennerholm, Kristina; Crescitelli, Rossella; Lässer, Cecilia; Gribonika, Inta ; 0000-0002-5694-1315; Lötvall, Jan (Journal of Extracellular Vesicles, 2021)
Bacterial outer membrane vesicles (OMV) have gained attention as a promising new cancer vaccine platform for efficiently provoking immune responses. However, OMV induce severe toxicity by activating the innate immune system. In this study, we applied a simple isolation approach to produce artificial OMV that we have named Synthetic Bacterial Vesicles (SyBV) that do not induce a severe toxic response. We also explored the potential of SyBV as an immunotherapy combined with tumour extracellular vesicles to induce anti-tumour immunity. Bacterial SyBV were produced with high yield by a protocol including lysozyme and high pH treatment, resulting in pure vesicles with very few cytosolic components and no RNA or DNA. These SyBV did not cause systemic pro-inflammatory cytokine responses in mice compared to naturally released OMV. However, SyBV and OMV were similarly effective in activation of mouse bone marrow-derived dendritic cells. Co-immunization with SyBV and melanoma extracellular vesicles elicited tumour regression in melanoma-bearing mice through Th-1 type T cell immunity and balanced antibody production. Also, the immunotherapeutic effect of SyBV was synergistically enhanced by anti-PD-1 inhibitor. Moreover, SyBV displayed significantly greater adjuvant activity than other classical adjuvants. Taken together, these results demonstrate a safe and efficient strategy for eliciting specific anti-tumour responses using immunotherapeutic bacterial SyBV.
© 2021 The Authors. Journal of Extracellular Vesicles published by Wiley Periodicals, LLC on behalf of the International Society for Extracellular Vesicles.
Keywords: Adjuvants, Immunologic/metabolism; Animals; Artificial Cells/immunology; Bacterial Outer Membrane/immunology; Cell Line, Tumor; Cytokines/metabolism; Dendritic Cells; Escherichia coli/immunology; Extracellular Vesicles/immunology; Humans; Immune Checkpoint Inhibitors/therapeutic use; Immunization; Immunotherapy; Melanoma, Experimental/immunology; Mice; Mice, Inbred C57BL; Th1 Cells/immunology